Evaluation and Analysis of Baitul Arqam on the Morals and Performance of Lecturers and Employees of the University of Muhammadiyah Kotabumi: Evaluasi dan Analisis Baitul Arqam terhadap Akhlak dan Kinerja Dosen dan Karyawan Universitas Muhammadiyah Kotabumi - Junaidi, Junaidi; Dinata, Karsoni Berta; Darwanto, Darwanto (Universitas Muhammadiyah Sidoarjo, 2020)
The aims of this study is as basis for making policies and strategies that need to be taken to improve the quality of Baitul Arqam Program going forward. Baitul Arqam program that has been carried out so far has never been seen in measurable terms. There are three research designs in this study, namely 1) descriptive-qualitative research design, 2) survey research design and 3) CIPP evaluation research design. The result of this study are based on the result of the analysis of the questionnaire and interview, it can be concluded that the lecturers and employees who have participated in Baitul Arqam activities have good morals and high performance. Based on the result of the evaluation it can be concluded that, 1) Baitul arqam material should be made into one book and distributed to participants, 2) The material should also discuss matters related to prayer, organizing bodies, and other worship in accordance with the guidance of HPT, 3) The video interesting learning so that participants are more interested and focused, 4) Every lecturer and employee who has not yet followed the Baitul Arqam must participate in the activity, 5) There is a pre-test and post-test to measure the success of the participants, 6) the mandatory requirements of participants are declared to pass if they take Fathul Quthub and Tahajud Prayers, and follow the material for each session at a minimum 75%.